Progressive Muscle Relaxation Therapy in Hypertensive Elderly with Acute Pain - Permatasari, Resi; Susumaningrum, Latifa Aini; Kurdi, Fahruddin; Basri, Achmad Ali (Al-Hijrah Indonesia, 2023)
Hypertension is a major health problem that occurs in the elderly. The prevalence of hypertension increases with ageing. Pain is a problem that can be caused by several conditions, such as hypertension. Progressive muscle relaxation therapy can be used to lower blood pressure. This research aims to determine the application of progressive muscle relaxation therapy in the elderly who experience hypertension with acute pain nursing problems. This research uses a case report method that describes the case of Mrs A, who has acute pain nursing problems at Dahlia room, UPT PSTW Jember. Nursing care is provided comprehensively for three days with a duration of 15 minutes for each meeting. The results were obtained after being given nursing care with progressive muscle relaxation therapy interventions. Namely, there was a decrease in pain levels and complaints of pain with results on the first day pre-intervention blood pressure 150/100 mmHg post-intervention 140/90 mmHg, and pre-intervention pain complaints scale 5 NRS post-intervention 5 NRS. On the fifth day, the results of pre-intervention blood pressure were 140/90 mmHg, post-intervention 130/90 mmHg, and pre-intervention pain complaints 3 NRS, post-intervention 3 NRS. The average blood pressure for five days was pre-intervention 144/98 mmHg, post-intervention 134/90 mmHg, and pre-intervention pain complaints 4.2 NRS post-intervention 3.8 NRS. Progressive muscle relaxation therapy, which is carried out three times with a duration of 15 minutes, can have an effect on reducing blood pressure and reducing acute pain problems.